PENTINGNYA KOMUNIKASI KELUARGA TERHADAP PERKEMBANGAN REMAJA DAN FAKTOR YANG MENYEBABKAN KURANG EFEKTIFNYA KOMUNIKASI DALAM KELUARGA - Khairul Annuar; Nurus Sa’adah (CONS-IEDU, 2023)
Humans are social creatures who need good relationships with other people, and have the urge to relate to others and other drives such as curiosity, self-actualization, and so on, will be removed by communicating with each other. Because humans can always develop and are able to carry out social life, of course with communication that can be done anytime, anytime, by anyone and with anyone. So is communication for a child in the family who has a job to use in the community. Parents in a family become figures for children in the form of the same things, behavior, words formed by parents from parents. The key to the communication pattern in the family that is built will affect the child's parenting pattern. With good communication patterns, good parenting patterns will be created, the formation of children in the form of families as parents' efforts towards character that must be done from an early age is the basis of education. The formation of awareness as the basis of education is a manifestation of the formation of the child's personality